Effect of nitrogen rates on the whitefly (Bemisia tabaci) population infesting chilli (Capsicum annum L.) - M. Zurina,; M.N. Mohamad Roff,; A.B. Idris, (Universiti Kebangsaan Malaysia, 2010)
Bemisia tabaci (Gennadius) is considered the most important whitefly species harmful to agriculture. Experiments were conducted at MARDI Station in Jalan Kebun, Klang, Selangor from 9 September 2006 to 11 November 2007. The objective of this study was to evaluate the population of whitefly on chilli plants fertilised with different rates of nitrogen (0, 33, 43, 53 g/plant). The results showed that high rates of nitrogen treatment significantly (P<0.05) increased B. tabaci immature population as compared to lower rate treatments. The mean number of B. tabaci immature per plant stratum was significantly different (P<0.05) among plant strata as well as among the treatments. Generally, the mean number of B. tabaci eggs and larvae was significantly (P<0.05) greater in the upper strata than in the middle and lower plant strata. Whereas, the mean number of B. tabaci pupa was significantly greater in the lower strata than in the upper and middle plant strata. The mean number of B. tabaci immature was significantly different (P<0.05) among the sampling periods in all treatment. Generally, B. tabaci population was significantly greater during the early season and gradually declined as the season progressed except during the third and seventh week after transplanting.